(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Development of acquired idiopathic white patch on the skin is called vitiligo and around a nevomelanocytic nevus is called halo nevus. Our patient had a halo nevus in the forehead and vitiligo elsewhere. Complete remission of his vitiligo and halo nevus was achieved with topical tacrolimus ointment without incurring any harm to the patient. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 70-72